The effects of two different anaesthesia techniques on bispectral index values and awareness during off-pump coronary artery bypass grafting - Bestas, Azize; Yasar, Mehmet Akif; Bayar, Mustafa Kemal; Inalkac, Suheyla (My University, 2004)
Objective. The aim of this study was to evaluate Bispectral Index values and awareness during two different anaesthesia regimens (fentanyl-propofol and fentanyl-midazolam) in patients undergoing off-pump CABG surgery. Methods. Fifty patients were included in the study. Patients were premedicated with midazolam and were randomly divided into two groups. Anaesthesia was induced with fentanyl (7-15 ?g/kg), with either propofol (2-2.5 mg/kg, Group I) or midazolam (0.1-0.3 mg/kg, Group II) and vecuronium (0.1 mg/kg). Anaesthesia was maintained with fentanyl (15 ?g/kg/h) together with either propofol (6 mg/kg/h) or midazolam (0.1 mg/kg/h). Depth of anaesthesia was adjusted according to clinical signs and haemodynamic responses. The level of sedation was monitored with Bispectral index continuously, but these levels were not shown to the attending anaesthetist. Bispectral index values were recorded for nine phases. Twenty-four hours after the operation, the patients were interviewed to determine intraoperative awareness and recall. Results. In all patients, Bispectral index values were found to decrease after induction (in Group I, p = 0.005, in Group II, p = 0.008) with the mean values remaining below 60 for all phases. The differences between the groups were not statistically significant in inter-group comparison. No patients were noted to recall the sounds presented during the operation and the preoperative events. Conclusions. BIS monitoring with clinical signs may be used to assess the adequacy of both types of anaesthesia techniques as well as to detect awareness during off-pump CABG surgery. © Springer Science + Business Media, Inc. 2005.
Keywords: Awareness; Bispectral index; Fentanyl; Midazolam; Off-pump CABG; Propofol